Актуарна діяльність у страхуванні життя та страхуванні на випадок хвороби (у тому числі медичному страхуванні): особливості теорії та практики генетичної дискримінації. - Арич, М.І. (Вісник економічної науки України, 2025)
У роботі проаналізовані сучасні тенденції особливостей теорії та практики генетичної дискримінації під час актуарної діяльності у страхуванні життя та страхуванні на випадок хвороби (у тому числі медичному страхуванні). Систематизовано захворювання генетична інформація про ймовірність розвитку яких наразі найбільш часто використовується страховими компанія для оцінки страхових ризиків у страхуванні. Обґрунтовано, що для якісної інтерпретації генетичної інформації потрібно враховувати всі інші фактори про стан здоров’я заявника на страхування. При цьому, визначено, що наслідками неправильної інтерпретації генетичної інформації заявників на страхування можуть бути хибні актуарні розрахунки, генетична дискримінація, зростання/зниження вартості страхової послуги тощо. This article provides an in-depth examination of prevailing trends in the conceptual and applied dimensions of genetic discrimination within actuarial practices governing life insurance and critical illness insurance, including health insurance. Particular emphasis is placed on the expanding role of genetic information in underwriting procedures and actuarial risk stratification. The study systematizes categories of diseases for which genetic data concerning the probability of disease manifestation are most frequently utilized by insurance undertakings in the evaluation of insurance risks. It is convincingly argued that the valid and methodologically sound interpretation of genetic information necessitates a holistic assessment of the insurance applicant’s overall health profile, incorporating clinical, environmental, and behavioral determinants. The article demonstrates that the fragmented or erroneous interpretation of genetic data may result in distorted actuarial estimations, institutionalized forms of genetic discrimination, and economically unjustified adjustments in insurance premiums. Empirical cases of genetic discrimination arising in actuarial activities within the domains of life and health insurance are subjected to systematic analysis. The findings reveal that the most recurrent manifestations of genetic discrimination in insurance markets encompass: (1) outright denial of insurance coverage or the imposition of actuarially inflated premiums, particularly in relation to African Americans carrying the sickle cell anemia gene; (2) adverse modification of contractual conditions or refusal to insure individuals exhibiting a genetic predisposition to Huntington’s disease; and (3) exclusion from coverage under health insurance policies for individuals possessing gene mutations associated with an elevated risk of developing Long QT syndrome. The article further substantiates a set of regulatory and financial mechanisms aimed at mitigating genetic discrimination in insurance practice. These mechanisms include the application of individualized premium-setting models, the establishment of segregated insurance risk pools, and the partial subsidization of life insurance costs through public budgetary instruments.